Ricci-Bourguignon soliton on three dimensional para-Sasakian manifold - Yashaswini R; Nagaraja H.G. (Journal of Hyperstructures)
In the present paper we study Ricci-Bourguignon solitons on three dimensional para-Sasakian manifolds with potential vector field as a special vector field. We proved the conditions for such manifold to be isometric to hyperbolic space. Further, the nature of RB-soliton based on the value of real numbers $ρ$ is investigated.